Bunching estimation of the male breadwinner norm in Brazil - Souza, Kauany Batista de (2022)
We investigate the impact of the male breadwinner norm a cultural norm that establishes that a man should earn more than his wife on married females earning outcomes. Our work aims to verify if this identity norm shapes behavior, and we start by modelling it as an implicit tax on womens earnings. We estimate the labor supply response of a wife who is likely to just out-earn her husband and reacts by adjusting her earnings so as to not violate the gender norm. Using bunching techniques and a range of labor supply elasticities, we find that the breadwinner norm generates a sizable additional tax rate on female labor supply. Our preferred estimate suggests the social norm add a 32 percentage points implicit marginal tax on earnings for those women who out-earn their husbands with similar earnings. Additional extensions suggest that religiosity and age play a role on the implicit tax related to this gender norm.